Penerapan Metode Skimming Dalam Peningkatan Kemampuan Membaca Dalam Hati Pada Remaja - Muhammad Raffi Fadliansyah; Salma Zakiyah (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Reading silently is a type of reading that is often done by someone to seek information and increase knowledge. A person should have the ability to read as a means of communication. In reading ability, there are techniques that a person can use, one of which is the Skimming technique. The aim of this research is to see the application of the skimming technique in improving the ability to read silently in teenagers aged 17-20 years. The method used is descriptive, explaining clearly the data that has been found. Meanwhile, for this data collection technique, the author uses interview and observation techniques with the target respondents, then the data is recorded and data analysis is carried out. The data analysis technique in this research uses three stages, namely data reduction, presenting data, and drawing data conclusions. The results of this research show that the skimming technique is very effective and efficient when used for the ability to read silently. Through this technique, teenagers experience continuous improvement because they apply skimming techniques in their reading activities.